How do Latin American migrants in the USA stand on schooling premium? What does it reveal about education quality in their home countries?. Issue 6 (3rd September 2018) - Alonso-Soto, Daniel; Nopo, Hugo
Abstract : Purpose: Indicators for quality of schooling are not only relatively new in the world but also unavailable for a sizable share of the world's population. In their absence, some proxy measures have been devised. One simple but powerful idea has been to use the schooling premium for migrant workers in the USA (Bratsberg and Terrell, 2002). The purpose of this paper is to extend this idea and compute measures for the schooling premium of immigrant workers in the USA over a span of five decades. Design/methodology/approach: In this paper, the authors focus on the schooling premia for the Latin American and the Caribbean region and compare them to those of migrants from other regions, particularly from East Asia and Pacific, India, Northern Europe and Southern Europe, all relative to immigrants from former Soviet Republics. The available data allow us to measure such premia for workers who graduated from school, either at the secondary or tertiary levels, in their home countries between 1940 and 2010. Findings: The results show that the schooling premia in Latin America have been steadily low throughout the whole period of analysis. The results stand after controlling for selective migration in different ways. This contradicts the popular belief in policy circles that the education quality of the region has deteriorated in recent years. In contrast, schooling premium in India shows an impressive improvement in recent decades, especially at the tertiary level. Originality/value: In this paper, the authors extend the idea of computing schooling premium for migrant workers in the USA (Bratsberg and Terrell, 2002) and present comparative estimates of the evolution of schooling premia in 17 Latin American countries for both secondary and tertiary schooling levels.